THE EPHEMERAL NATURE OF BEAUTY AND TIME IN CAVALIER POETRY - Eldorbek Erkin og’li Khamitov; Nurymbetova Zumrad Ruslanovna (Ta’lim innovatsiyasi va integratsiyasi, 2025)
This study investigates the themes of transience, temporal beauty, and the fleeting nature of life in Cavalier poetry, a prominent literary movement of early seventeenth-century England. Poets such as Robert Herrick, Richard Lovelace, and Thomas Carew frequently emphasize the impermanence of youth, physical charm, and worldly pleasures, reflecting the cultural and philosophical concerns of their era. Through detailed analysis, the research explores how carpe diem motifs, striking imagery, and lyrical techniques convey the inevitability of aging and the urgency of embracing life’s fleeting joys. The study also considers the tension between moral conduct and indulgence in aesthetic and sensual pleasures, demonstrating the poets’ sophisticated approach to human desires and ethical considerations. By comparing several works within the Cavalier tradition, the paper identifies recurring stylistic traits, including clarity of language, musicality, and rhetorical elegance, which enhance the poems’ emotional resonance and persuasive effect. Ultimately, this research shows that Cavalier poetry not only celebrates the pleasures of life but also meditates on mortality and the passage of time. It reflects the broader social, cultural, and philosophical currents of seventeenth-century England, making it a valuable resource for understanding contemporary attitudes toward beauty, time, and human experience.